Door to balloon time in primary percutaneous coronary intervention in ST elevation myocardial infarction: every minute counts. Issue 5 (8th March 2022) - Marcusohn, Erez; Reiner Benaim, Anat; Ronen, Shay; Kerner, Arthur; Beyar, Rafael; Almog, Ronit
Abstract : Objectives: This study examines relationships between door to balloon (D2B) time and subsequent admissions due to heart failure (HF), acute coronary syndrome (ACS), and mortality for up to 1 year. Background: Current guidelines set 90-min for D2B time for primary percutaneous coronary intervention (PPCI) as a goal, which has been shown to reduce mortality and adverse events. Methods: Using the MDclone ADAMS system integrated with our electronic medical records, we conducted retrospective analysis of all patients admitted due to ST-elevation myocardial infarction from home, without any history of HF or coronary disease, and who underwent PPCI during 2013–2019. Data on D2B time, baseline clinical and demographic characteristics, and outcomes of HF, ACS and mortality were collected. Adjusted HR for each of the outcomes was calculated by multivariate Cox model. Results: A total of 826 patients were included in the final analysis. D2B had no significant effect on incidence of heart failure admissions for up to 1-year follow-up. D2B had a significant effect on mortality at 180 days, showing a 30% increase for each 30-min increase (HR 1.308; CI, 1.046–1.635) as for ACS at 90 days (HR 1.307; 1.025–1.638). The 30-min D2B cutoff showed a significant increase in ACS recurrence throughout the follow-up period at 90 days (HR 2.871, 1.239–6.648), 180 days (HR 2.607, 1.255–5.413), and 1 year (HR 1.886, 1.073–3.317). Conclusions: Patients with shorter D2B times had significantly reduced mortality and recurrence of ACS, with no effect on heart failure admission incidence.